Experimental Study and Mathematical Modeling of the Processes Occurring in ZrN Coating/Silumin Substrate Systems under Pulsed Electron Beam Irradiation; Coatings; Vol. 11, iss. 12 - Koval N. N. Nikolay Nikolaevich; Koval T. V. Tamara Vasilievna; Krysina O. V. Olga Vasiljevna; Ivanov Yu. F. Yury Fedorovich; Teresov A. D. Anton Dmitrievich; Moskvin P. V. Pavel Vladimirovich; My Kim An Tran; Prokopenko N. A. Nikita Andreevich; Petrikova E. A. Elizaveta Alekseevna (2021, 2021)
Title screen